Pengaruh Penerapan Standar Akuntansi Keuangan dan Tax Planning Terhadap Kualitas Laporan Keuangan UMKM Kabupaten Karawang - Yanti; Rohma Septiawati; Siti Nur Haliza (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to evaluate and test the effect of implementing EMKM financial accounting standards and tax planning on the quality of MSME financial reports in Karawang Regency. This research uses quantitative methodology with primary data collection. The sample for this research only consists of MSMEs based in Karawang Regency. The number of samples for this research was one hundred respondents. This research focuses on MSMEs in Karawang Regency. Using PLS and SmartPLS 3.0, analyze the relationship between dependent and independent variables. The findings of this research show that the application of EMKM accounting standards and tax planning has a positive and significant effect on the quality of MSME financial reports.